The plant ovule secretome: a different view toward pollen-pistil interactions - Liu, Y.; Joly, V.; Dorion, S.; Rivoal, J.; Matton, D. P.
During plant sexual reproduction, continuous exchange of signals between the pollen and the pistil (stigma, style, and ovary)plays important roles in pollen recognition and selection, establishing breeding barriers and, ultimately, leading to optimal seed set. After navigating through the stigma and the style, pollen tubes (PTs)reach their final destination, the ovule. This ultimate step is also regulated by numerous signals emanating from the embryo sac (ES)of the ovule. These signals encompass a wide variety of molecules, but species-specificity of the pollen-ovule interaction relies mainly on secreted proteins and their receptors. Isolation of candidate genes involved in pollen-pistil interactions has mainly relied on transcriptomic approaches, overlooking potential post-transcriptional regulation. To address this issue, ovule exudates were collected from the wild potato species Solanum chacoense using a tissue-free gravity-extraction method (tf-GEM). Combined RNA-seq and mass spectrometry-based proteomics led to the identification of 305 secreted proteins, of which 58 per cent were ovule-specific. Comparative analyses using mature ovules (attracting PTs)and immature ovules (not attracting PTs)revealed that the last maturation step of ES development affected almost half of the ovule secretome. Of 128 upregulated proteins in anthesis stage, 106 were not regulated at the mRNA level, emphasizing the importance of post-transcriptional regulation in reproductive development.
Keywords: POLLEN?PISTIL INTERACTIONS; OVULE EXUDATES; SECRETOME; CHEMOATTRACTION; POLLEN TUBE GUIDANCE; GEL-FREE NANO-LC?MS/MS; LABEL-FREE QUANTIFICATION